Oxford new syllabus primary mathematics workbook 5A - Yee, Dr Foong Pui (Karachi Oxford university press, 2019)
The *Oxford New Syllabus Primary Mathematics Workbook 5A* is designed to support primary-level students in mastering mathematical concepts through engaging and structured exercises. Aligned with the latest curriculum standards, this workbook emphasizes problem-solving, critical thinking, and application of mathematical skills in real-world contexts. It features clear explanations, varied practice questions, and activities that encourage active learning, making it an essential resource for building a strong foundation in mathematics.